Pengaruh Person Job-Fit Dan Stres Kerja Terhadap Kepuasan Kerja Karyawan (Studi pada Karyawan Outsource Bank BCA KCU Madiun) - Metik Asmike; Bagus Setiono (CAPITAL: Jurnal Ekonomi dan Manajemen, 2020)
PT. Bank Central Asia Tbk, branch office Madiun is a private company engaged in banking. The purpose of this study are to determine the effect of person job-fit and job stress on job satisfaction in outsourced employees of Bank BCA KCU Madiun. This research is a quantitative study with data collection techniques through questionnaires distributed to employees. Sampling of this study using a questionnaire. With a population of 50 outsourced employees. The collected data is then processed using multiple linear regression analysis. The results of the test found that: (1) There is a significant influence between job-fit person on job satisfaction; (2) There is a significant negative effect between job stress on job satisfaction on Outsourced Bank BCA KCU Madiun employees.Keywords: Person Job-Fit, Job Stress and Job Satisfaction